Exhibition Reviews. Issue 1 (1st July 2022) - Hilton-Smith, Simon; Weiser, M. Elizabeth; Russ, Sarah; Hussey, Kristin; Grist, Penny; Carfora, Natalie; Wilson-Hokowhitu, Nalani; Chen, Fei; Zheng, Yi; Guan, Xiaorui
Abstract : [Re:]Entanglements: Colonial Collections in Decolonial Times, Museum of Archaeology and Anthropology, University of Cambridge (22 June 2021 to 20 April 2022) Greenwood Rising Center, Tulsa, Oklahoma First Americans: Tribute to Indigenous Strength and Creativity, Volkenkunde, Leiden, the Netherlands (May 2020 to August 2023) Kirchner and Nolde: Up for Discussion, Statens Museum for Kunst, Copenhagen (April–August 2021) Australians & Hollywood, National Film and Sound Archive, Canberra Free/State : The 2022 Adelaide Biennial of Australian Art, Art Gallery of South Australia, Adelaide (4 March–5 June 2022) Te Aho Tapu Hou: The New Sacred Thread, Waikato Museum Te Whare Taonga o Waikato (7 August 2021 to 9 January 2022) West Encounters East: A Cultural Conversation between Chinese and European Ceramics, Shanghai Museum (28 October 2021 to 16 January 2022) The Shanghai Jewish Refugees Museum's Permanent Exhibition, Shanghai The Way of Nourishment: Health-preserving Culture in Traditional Chinese Medicine, The Chengdu Museum, Chengdu, Sichuan Province, China (29 June–31 October 2021)